Estadiamento do carcinoma papilar de tireoide: associação entre a ultrassonografia pré-operatória e achados cirúrgicos - Juliana de Brito Brandao (2013)
Introduction: Papillary thyroid carcinoma is the most common thyroid malignancy, accounting for 85% of all thyroid cancers. The cause-specific 10-year survival rate exceeds 90%, but recurrence occurs in up to 30% patients. Cervical lymph node metastasis is common and it is considered an important risk factor for local recurrence. The lymph node involvement occurs most commonly at the central compartment, and detection on palpation in this region is often difficult. Recently, the US is the method of choice for preoperative staging of both tumor and lymph node, determining the surgical strategy. However, there are few studies that evaluated the correlation of US with histopathologic examination (AP). Aims: To evaluate the association of preoperative ultrasonographic staging with postoperative staging in the two most widely used surgical procedures in the management of papillary thyroid carcinomas (PTC): total thyroidectomy (TT) with systematic central compartment neck dissection (CND) and TT with removal of the clinically involved lymph nodes (LN), in order to determine the accuracy of ultrasonography (US) compared with the histological assessment. We also aim, to assess the impact of these surgical procedures on PTC staging and to investigate clinical factors that may be considered predictors of lymph node involvement. Patients and Method: The study included 98 patients with preoperative diagnosis of PTC by fine-needle aspiration (FNA) biopsy who underwent total thyroidectomy and had preoperative US and AP examination reports on record. All patients underwent preoperative US, performed by a single radiologist. The patients were operated on by two teams of surgeons with extensive experience in thyroid surgery, who adopted distinct forms of surgical management: TT with compartment VI dissection (TT+ CND) (group 1) or TT with selective removal of the involved LNs by clinical or sonographic criteria (group 2). The results of US and AP staging based on TNM were compared for each group. Results: The mean accuracy of preoperative US for tumor category assignment was 69.4%. Sonographic accuracy for stages T1, T2, T3 and T4 was 77.6%, 66.7%, 43% and 0%, respectively. Lymph node involvement occurred in 34% of the patients in group 1 and 7.1% in group 2. Sensitivity, specificity, positive predictive value, and negative predictive value of US for detection of lymph nodal metastasis were 36.8%, 100%, 100% and 75.5% in group 1. The association of US and AP in relation to lymph node involvement could not be determined in group 2 due to surgical technique used. The accuracy of US in establishing lymph nodal status N0, N1a and N1b was 100%, 16.7% and 57% in group 1. Only multicentricity had a statistically significant relationship with lymph node involvement. Conclusion: Despite being the test of choice for staging thyroid cancer, preoperative US yielded low sensitivity both for detection of central compartment LNs and diagnosis of extrathyroidal extension. The adopted surgical management is determinant in the nodal involvement evaluation and postoperative staging.